Changes in protein and gene expression of angiotensin II receptors (AT1 and AT2) in aorta of diabetic and hypertensive rats. (2nd January 2016) - Romero-Nava, R.; Rodriguez, J. E.; Reséndiz-Albor, A. A.; Sánchez-Muñoz, F.; Ruiz-Hernandéz, A.; Huang, F.; Hong, E.; Villafaña, S.
Abstract: Diabetes and hypertension have been associated with cardiovascular diseases and stroke. Some reports have related the coexistence of hypertension and diabetes with increase in the risk of developing vascular complications. Recently some studies have shown results suggesting that in the early stages of diabetes and hypertension exist a reduced functional response to vasopressor agents like angiotensin II (Ang II), which plays an important role in blood pressure regulation mechanism through the activation of its AT1 and AT2 receptors. For that reason, the aim of this work was to study the gene and protein expression of AT1 and AT2 receptors in aorta of diabetic SHR and WKY rats. Diabetes was induced by the administration of streptozotocin (60 mg/kg i.p.). After 4 weeks of the onset of diabetes, the protein expression was obtained by western blot and the mRNA expression by RT-PCR. Our results showed that the hypertensive rats have a higher mRNA and protein expression of AT1 receptors than normotensive rats while the AT2 expression remained unchanged. On the other hand, the combination of diabetes and hypertension increased the mRNA and protein expression of AT1 and AT2 receptors significantly. In conclusion, our results suggest that diabetes with hypertension modifies the mRNA and protein expression of AT1 and AT2 receptors. However, the overexpression of AT2 could be associated with the reduction in the response to Ang II in the early stage of diabetes.